The Green and Low-Carbon Development Effect of Comprehensive Sports Events: A Quasi-Natural Experiment From China - Zhang, Xingmin; Wu, Yihan (Frontiers in Environmental Science, 2022)
Large-scale sports events can improve public environmental awareness, strengthen urban governance and push green innovation. However, it may also increase the burden of infrastructure, cause energy consumption and lead to some pollution. Using the panel data of 278 cities in China from 2006 to 2019, this paper systematically discusses how comprehensive sports events affect the green and low-carbon development of Chinese cities. Firstly, the green total factor productivity and carbon emission efficiency calculated by SBM-DEA model are taken as proxy variables of green and low-carbon development. And then the spatial difference-in-differences (SDID) model is employed to undertake empirical analysis and further test the impact mechanism and heterogeneity. Four main results are derived from this paper. (1) The hosting of comprehensive sports events can significantly enhance the green and low-carbon development of cities. This result is still valid after a whole string of robustness tests. (2) Comprehensive sports events have a significant positive spatial spillover effect on the green and low-carbon development of adjacent cities. (3) The mechanism analysis shows that comprehensive sports events can encourage green development of cities through technological innovation, sports industry development as well as foreign investment, but through foreign investment, sports events cannot significantly affect the green total factor productivity and carbon emission efficiency of host cities. (4) Heterogeneity exists between the city rank and the event level. The promotional effect of comprehensive sports events on cities' green and low-carbon development is more significant in first-tier cities and international events.